Hydrogen and Propane Production From Butyric Acid Photoreforming Over Pt-TiO2 - Scandura, Gabriele; Rodríguez, Jorge; Palmisano, Giovanni (Frontiers in Chemistry, 2019)
Photocatalysis is a promising technology from economic, energetic, and ecological points of view because it takes advantage of solar light. Hence, it is one of the investigated green routes to produce hydrogen from renewable energy resources. Butyric acid (BA) is largely present in wastewater and as an intermediate product in anaerobic digestion and therefore it is an inexpensive resource, which can be converted to valuable chemicals. In this work, photoreforming of butyric acid (BAPR) under UV light in aqueous suspensions of platinum-modified titanium dioxide-based catalysts is reported for the first time. Titania nanotubes (TNT) synthesized and calcined at different temperatures (300, 400, 500°C) and commercial TiO2 (P25), decorated with platinum nanoparticles, have been tested and characterized through different techniques including X-ray powder diffraction, UV-vis diffuse reflectance and photoluminescence spectroscopy, transmission electron microscopy, BET and porosimetry analysis. The main identified products of the BAPR were H2, propane, CO2 and several organic acids (e.g., pentanoic and 3-methylhexanoic acid). It has been found that the morphology and crystallinity of the photocatalysts affected dramatically their optical properties and, consequently, the reaction rate and the product distribution. Specifically, the highest conversion of BA (XBA) and selectivity toward H2 (SH2) was recorded with P25-Pt (XBA = 26.9%, SH2 = 47.2% after 8 h of irradiation). TNT-400-Pt showed the highest selectivity toward propane (SC3H8 = 16.1%) with XBA = 23.4% and SH2 = 36.2%. The activity results in conjunction with the characterization of the catalysts highlighted that the main factor affecting the activity in terms of XBA and generation of H2 was the crystallinity, and in particular the presence of rutile phase in TiO2, whereas SC3H8 appears to increase when the electron-holes recombination is lower.